Superconductivity in Li-intercalated bilayer arsenene and hole-doped monolayer arsenene: a first-principles prediction. (21st May 2018) - Chen, Jianyong; Ge, Yanfeng; Zhou, Wenzhe; Peng, Mengqi; Pan, Jiangling; Ouyang, Fangping
Abstract: Using first-principles calculations, we find Li-intercalated bilayer arsenene with AB stacking is dynamically stable, which is different from pristine bilayer with AA stacking. Electron–phonon coupling of the stable Li-intercalated bilayer arsenene are dominated by the low frequency vibrational modes ( E ″(1), (1), E ′(1) and acoustic modes) and lead to an superconductivity with T c   =  8.68 K with isotropical Eliashberg function. Small biaxial tensile strain (2%) can improve T c to 11.22 K due to the increase of DOS and phonon softening. By considering the fully anisotropic Migdal–Eliashberg theory, T c are found to be enhanced by 50% and exhibits a single anisotropic gap nature. In addition, considering its nearly flat top valence band which is favorable for high temperature superconductivity, we also explore the superconducting properties of hole-doped monolayer arsenene under different strains. the unstrained monolayer arsenene superconducts at T c   =  0.22 K with 0.1 hole/cell doping. By applying 3% biaxial strain, T c can be lifted up strikingly to 6.69 K due to a strong Fermi nesting of the nearly flat band. Then T c decreases slowly with strain. Our findings provide another insight to realize 2D superconductivity and suggest that the strain is crucial to further enhance the transition temperature.